(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
With a 43-year trajectory in Brazilian scenic lighting, Margarete (Marga) Ferreira is one of the first women to join the lighting profession. In this interview, she tells us stories about her early career as a light operator until her acknowledgment as a light creator, acting in theater shows, puppet theater, operas and, mainly, in music shows, where she worked with artists such as Adriana Calcanhotto, Engenheiros do Hawaii, Cassia Eller and Leila Pinheiro. Her reports show us how empirical her professional development is (from different experiences on making light); give evidence of how this profession was consolidated in Brazil and reveal the difficulties faced by women in this area of expertise.